Study of Lignin Extracted from Rubberwood Using Microwave Assisted Technology for Fuel Additive - Trakarn Yimtrakarn; Watchareeya Kaveevivitchai; Wen-Chien Lee; Nuttapol Lerkkasemsan (My University, 2022)
Lignin is the most abundant natural aromatic polymer, especially in plant biomass. Lignin-derived phenolic compounds can be processed into high-value liquid fuel. This study aimed to determine the yield of lignin by the microwave-assisted solvent extraction method and to characterize some essential properties of the extracted lignin. Rubberwood sawdust (Hevea brasiliensis) was extracted for lignin with an organic-based solvent, either ethanol or isopropanol, in a microwave oven operating at 2450 MHz. Two levels of power of microwave, 100 W and 200 W, were tested as well as five extraction times (5, 10, 15, 20, 25, and 30 min). The extracted lignin was characterized by Klason lignin, Fourier transform infrared spectroscopy (FT-IR), 2D HSQC NMR, Ultraviolet-visible spectrophotometry (UV-vis), and Bomb calorimeter. The results showed that the yield of extracted lignin increased with the extraction time and power of the microwave. In addition, the extraction yield with ethanol was higher than the yield with isopropanol. The highest yield was 6.26 wt.%, with ethanol, 30 min extraction time, and 200 W microwave power.
Keywords: Sawdust; Lignin and Wood Chemistry